The role of village-owned enterprises in achieving sustainable development goals (SDGs) in Wajo Regency - Kalsum, Ummi; Nurlinah; Irwan, Andi Lukman (Department of Government Science, 2024)
Village Sustainable Development Goals (SDGs) is a sustainable development effort that contains eighteen goals that touch all aspects of life, including village economic growth. Village-owned enterprises (BUMDes) are instruments used to improve economic development and village welfare. This study discusses how the role of BUMDes in achieving the 8th village SDGs goal, namely equitable village economic growth. This study aims to find out how the implementation and management of BUMDes in achieving Village SDGs and factors that influence the role of BUMDes in achieving the 8th Village SDGs goal in Gilireng District. The research type was descriptive qualitative, which collected data from observations, interviews, literature studies, and documentation studies. The study reveals that the contribution of BUMDes in increasing Village Original Income (PAD) has not been optimal, and BUMDes have not been able to provide job opportunities for rural communities. BUMDes in Gilireng District have not been able to encourage the achievement of Village SDGs because they were influenced by several factors: the human resources competency that remains limited and external conditions such as economic and political factors. However, BUMDes in Gilireng District has the potential and opportunity to become pillars of village economic development. Therefore, it is crucial for the relevant government to step in and improve the qualifications of BUMDes managers in the Gilireng District.